A comparative analysis of methods of preinduction cervical ripening and induction of labor in Poland and in Germany (Part II): maternal and neonatal outcomes - Agnieszka K. Kleszcz; Dorota Ćwiek; Olimpia Sipak-Szmigiel (BMC Pregnancy and Childbirth)
Abstract The benefits and risks of delivery should always be considered before initiating preinduction cervical ripening and labor induction. Understanding the benefits and potential complications is crucial for healthcare professionals to make informed decisions and provide optimal care. The research was conducted retrospectively between January 2019 and July 2022. It involved the analysis of the medical records of 154 pregnant women staying in the Clinic of Obstetrics and Gynecology in the city of Szczecin and 150 pregnant women hospitalized in the Clinic of Obstetrics and Gynecology in the town of Schwedt/Oder in Germany. Inclusion criteria were consent to participate and the implementation of internal written protocols in line with national guidelines for labor induction. The research concerned a group of pregnant women with postdate pregnancy, calculated according to the Naegele’s rule and confirmed by the USG examination conducted in the first trimester of the pregnancy, as well as an unfavorable cervix that received less than 6 points in the Bishop score. Moreover, the pregnant patients with a low biophysical profile and an abnormal record of CTG or comorbidities were also included, as these factors determined the classification of the group above. The study did not include patients who had undergone cesarean section. The average change in evaluation of the cervix marked on the Bishop Score was higher in Germany, and it was 2.7 points, whereas in Poland, it was 1.6 points. The largest percentage of the scores on the Apgar Scale in the first, third and fifth minutes after birth was in the norm and indicated a good health condition of infants. They reached 8 to 10 points in both countries. Significantly more infants in Germany received pH from the umbilical cord within the limits of the norm. And it marks the welfare of neonates (7.20–7.45). The duration of hospitalization in Poland was shorter than in Germany. It was 3.8 days in the case when the median equalled 3. The number of days of preinduction cervical ripening and induction was similar in both countries. The levels of haemoglobin were comparable in both countries. The most common postpartum complications in Poland and Germany were first-degree perineal tears, episiotomies and anemia. Among the postpartum complications, cervical tears, revision of the uterine cavity, and episiotomy were significantly more common in Poland. First- and second-degree perineal tears were more frequent in Germany.